1972
DOI: 10.1111/j.1365-2265.1972.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of Cortisol and Synthetic Corticosteroids in Man

Abstract: SUMMARYFollowing the rapid intravenous injection of corticosteroids (cortisol, prednisolone, betamethasone and betamethasone‐17‐valerate), the blood levels of each were estimated and the results analysed in a two‐compartment open model. The kinetic analysis revealed differences in distribution and elimination which could have important therapeuticimplications. A theory is presented for the marked differences seen, and the therapeutic importance of these is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Whilst this is clearly important in understanding its physiological role, there is a broader context in that 2-3% of the population of the UK and USA are prescribed therapeutic glucocorticoids, including dexamethasone, prednisone and prednisolone [37,38]. It is well established that synthetic glucocorticoids are poorly metabolized within human tissues, and demonstrate poor cortisol binding globulin affinity and slower plasma removal rates, thus having more prolonged action when compared to endogenous glucocorticoids [39][40][41]. However, several studies have shown that synthetic glucocorticoids can also be inactivated through a variety of metabolic pathways, including oxidation or reduction by CYP3A4, isoforms of 11β-HSD and 5αR [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this is clearly important in understanding its physiological role, there is a broader context in that 2-3% of the population of the UK and USA are prescribed therapeutic glucocorticoids, including dexamethasone, prednisone and prednisolone [37,38]. It is well established that synthetic glucocorticoids are poorly metabolized within human tissues, and demonstrate poor cortisol binding globulin affinity and slower plasma removal rates, thus having more prolonged action when compared to endogenous glucocorticoids [39][40][41]. However, several studies have shown that synthetic glucocorticoids can also be inactivated through a variety of metabolic pathways, including oxidation or reduction by CYP3A4, isoforms of 11β-HSD and 5αR [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…One compound often mentioned as a potential vehicle is citric acid (6)(7)(8)(9)(10)(11)(12). In the crystalline state, this material is highly hydrogen bonded (13), a property that apparently is responsible for its glass formation, because it has been reported that hydrogen bonding tendency helps prevent crystallization from occurring when a liquid melt is cooled below its liquidus temperature (14-16).…”
Section: Communica Tionsmentioning
confidence: 99%
“…The thermal stability of citric acid has been of concern to previous solid dispersion investigators (6)(7)(8)(9)(10)12). Available thermal analysis literature on citric acid is limited.…”
Section: Communica Tionsmentioning
confidence: 99%
“…Following the intravenous injection of [14C]cortisol (Fell 1972) the half-time of disappearance was somewhat shorter than normal in the 'peripheral' pool (i.e. plasma) but slightly prolonged in the 'central' pool (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma immunoreactive n-ACTH was determined using the method of Rees et al (1971). Urinary steroid profiles were estimated by gas liquid chromatography (Trafford 8c Makin 1972) and the halflife of [14C]cortisol in 'central' and 'peripheral' pools was measured using the method of Fell (1972). The binding capacity of CBG in pre-operative plasma (see Fig.…”
Section: Methodsmentioning
confidence: 99%